Исследования теплового режима газофазного окисления алмазно - графитной смеси - Гринь, Григорий Иванович; Козуб, П. А.; Синицкая, А. М. (НТУ "ХПИ", 2005)
The data on kinetic of oxidation of a diamond graphite mixture (DGM) are given. Positive influence of admixture of vanadium on process of oxidation DGM is shown and mechanism of interaction of vanadium oxide at the presence of oxygen of air with graphite is proposed. The influence of various technological parameters on overheating of DGM layer is given.
Keywords: алмазографитовая шихта; кинетика окисления